PENERAPAN METODE FINITE STATE MACHINE PADA GAME PANDEMIC NIGHTMARE BERBASIS ANDROID - Khafidh Aulia, Muhammad; Mahmudi, Ali; Achmadi, Sentot (JATI (Jurnal Mahasiswa Teknik Informatika), 2021)
The Covid-19 pandemic has limited activities outside the home. One of the government's efforts to break the chain of spreading the Covid-19 virus is to urge people to stay at home and carry out all work and study activities online. To get rid of boredom during a pandemic, researchers took the initiative to make a game about teenage nightmares during a pandemic that can be played on Android devices. This research is the creation of an Android-based Pandemic Nightmare game. The method used is FSM (Finite State Machine) as the artificial intelligence of the NPC (Non Playable Character) character in the Pandemic Nightmare game. The need for the thesis product being developed includes Unity 3D as a game engine and Android as a test device. The results of this research are a product in the form of a game that can be run on devices with an Android operating system at least version 5.0 Lollipop. These products have features such as touch controls on the smartphone screen, NPCs that have artificial intelligence, items that can be collected at each level, sound settings, level selection, and fear features that can reduce player visibility. Based on the features contained in the Pandemic Nightmare game, all features can function properly and correctly. Based on user testing, it is known that the majority of users think the games developed are good. Based on the results of the study, it can be concluded that artificial intelligence with the FSM (Finite State Machine) method functions properly, the control buttons and menu buttons function properly. Based on user testing, the Pandemic Nightmare game is good and worth playing.